Analysis of Optimization of the Use of Personal Protective Equipment in the Loading and Unloading Process of Goods at Sorong Port - Karubaba, Oktovianus Cristian; Sumarta, Ryan Puby; Widarbowo, Dodik; Nalle, Carles Yerid Absalom (International Journal of Science and Society, 2024)
This study aims to analyze the optimization of the use of Personal Protective Equipment (PPE) in the loading and unloading process at the Port of Sorong, Southwest Papua, in line with the Regulation of the Minister of Manpower and Transmigration Number PER.08/MEN/VII/2010. With a qualitative descriptive approach, data were collected through observation and in-depth interviews with workers, supervisors, and port management. The results of the study indicate that although PPE has been provided in accordance with the standards, the level of worker compliance is still low, mainly due to discomfort and lack of awareness of the importance of work safety. In addition, suboptimal supervision and unclear sanctions also contribute to low compliance. This study recommends increased supervision, stricter implementation of sanctions, and the provision of more ergonomic PPE to improve occupational safety and operational efficiency at Sorong Port.